Facts behind the behavioral intention to use the GO-JEK application - Dien Mardhiyah, Romario Simangunsong, (Opción, 2020)
This study aims to determine the effect of perceived usefulness, perceived ease of use, attitude toward using, and several external factors (perceived self-efficacy and perceived convenience) on behavioral intention to use GO-JEK applications using the TAM model. This study uses a quantitative approach. As a result, perceived usefulness, perceived ease of use, attitude toward using, and several external factors (perceived self-efficacy and perceived convenience) influence behavioral intention. In conclusion, users with a positive outlook, after trying the GO-JEK application for the first time, will evaluate the use of the application.